1999
DOI: 10.1046/j.1369-6513.1999.00033.x
|View full text |Cite
|
Sign up to set email alerts
|

Minority ethnic community participation in needs assessment and service development in primary care: perceptions of Pakistani and Bangladeshi people about psychological distress

Abstract: OBJECTIVES: To promote community participation in exploring perceptions of psychological distress amongst Pakistani and Bangladeshi people, in order to develop appropriate services. DESIGN: Training and facilitation of resident community members (as community project workers), to define and conduct qualitative research involving semistructured interviews in their own communities, informing primary care led commissioning and service decision making. Setting A socio-economically disadvantaged inner-city locality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
33
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 18 publications
4
33
0
Order By: Relevance
“…The literature already describes a range of benefits resulting from the use of community based research (see Kai and Hedges 1999, Rhodes et al 2002, Rowe 2006) and many were similarly reported here.…”
Section: Benefits Associated With Working As a Researchersupporting
confidence: 61%
See 1 more Smart Citation
“…The literature already describes a range of benefits resulting from the use of community based research (see Kai and Hedges 1999, Rhodes et al 2002, Rowe 2006) and many were similarly reported here.…”
Section: Benefits Associated With Working As a Researchersupporting
confidence: 61%
“…South et al (2012) also call for attention to be given to the difference between formal and informal roles, as well as spectrums of participation along which researcher roles are located. Thus, more analysis is needed particularly in relation to the unquestioned assumptions reported about the positive experiences of lay researchers within numerous studies (Newell & South 2009, see Rowe 2006, Kai and Hedges 1999, Rhodes et al 2000. It may also be the case that there has simply been a lack of consideration of the issues associated with the personal implications of working within a lay researcher role (Newall and South 2009).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, their female counterparts are more inclined to use ruminative coping strategies, with the focus being more on cause and consequences rather than cure. This difference in coping style is evident among older adults in the South Asian community where men are more involved in outdoor activities and have wider social networks and more interaction with the outside world than the older South Asian women (Agarwal 1998;Kai 1999;Mathuranath et al 2005;Sudha et al 2007). …”
Section: Discussionmentioning
confidence: 99%
“…South A small number of studies have examined the experiences of community members who have been involved in the research process, and findings indicate that participation has a positive impact. For example, increases in knowledge, skills, and confidence have all been reported (Kai & Hedges, 1999;Lindsey & McGuinness, 1998;Rhodes et al, 2002;Rowe, 2006). Furthermore, Lindsey and McGuinness (1998), Rhodes et al (2002), and Rowe (2006) found that, through their involvement, participants had developed greater empathy and understanding of others within their community.…”
Section: Introductionmentioning
confidence: 93%
“…Furthermore, Lindsey and McGuinness (1998), Rhodes et al (2002), and Rowe (2006) found that, through their involvement, participants had developed greater empathy and understanding of others within their community. Participation has also been described as a satisfying and rewarding experience by lay researchers (Kai & Hedges, 1999;Lindsey & McGuinness, 1998). Rowe (2006) further reported that for some of the parent researchers in her study, their involvement had led them to take up further educational courses and opportunities.…”
Section: Introductionmentioning
confidence: 98%